Interdisciplinary oral and primary health care for patients with disabilities - Etminan, Sodabeh; Hammerdahl, Elsa; Lesondak, Linda; Li, Nicole; Patel, Manav; Mischler, Matthew; Keehn, Mary; Kirschner, Kristi (Frontiers in Medicine, 2025)
IntroductionIndividuals with intellectual and developmental disabilities (IDD) often face access to care barriers due to limited provider training, inadequate appointment availability, transportation barriers, financial limitations, and insufficient interdisciplinary collaboration. As a result, this group is particularly vulnerable to oral health issues, experiencing higher rates of periodontal disease and dental caries compared to those without disabilities. Survey data from both dentists and caregivers highlights these obstacles, revealing that a significant proportion of providers do not treat individuals with cognitive disabilities, and patients with IDD often seek care on an emergency basis. This study explores whether a specialized model of dental care—featuring longer appointment times, desensitization techniques, accessible dental furniture, and an interdisciplinary, collaborative team of providers trained to work with individuals with disabilities—can improve dental and overall health outcomes.MethodsA total of 50 participants aged 18 years or older with an intellectual or developmental disability (IDD) diagnosis were recruited from a Federally Qualified Health Center (FQHC). Participants were identified by a physician specializing in IDD. Participants who consented were provided with an iPad to complete a 20-min electronic REDCap survey assessing their experiences at Mile Square Health Center, prior dental visits, and barriers to care.ResultsLonger appointment times, accessible dental furniture, and providers with training in treating patients with IDD appeared to significantly improve the patient experience.DiscussionThe findings suggest that longer appointment times, a non-coercive approach, and improved referral and transportation pathways can positively enhance both treatment outcomes and patient satisfaction. This study also emphasizes the importance of interdisciplinary collaboration in developing referral pathways and integration of dental care within the broader healthcare services for individuals with IDD as a model care delivery system.